Bayesian network analysis of panomic biological big data identifies the importance of triglyceride-rich LDL in atherosclerosis development - Voros, Szilard; Bansal, Aruna T.; Barnes, Michael R.; Narula, Jagat; Maurovich-Horvat, Pal; Vazquez, Gustavo; Marvasty, Idean B.; Brown, Bradley O.; Voros, Isaac D.; Harris, William; Voros, Viktor; Dayspring, Thomas; et al. (Frontiers in Cardiovascular Medicine, 2023)
Whether biomarkers other than low-density lipoprotein cholesterol (LDL-C) are causal in atherosclerosis is unknown. We analyzed 665 patients (mean±SD age, 56±11 years; 47% male) from the GLOBAL clinical study (NCT01738828). Cases were defined by the presence of any discernable atherosclerotic plaque based on comprehensive cardiac CT. De novo Bayesian networks built out of 37,000 molecular measurements and 99 conventional biomarkers per patient examined the potential causality of specific biomarkers. Most highly ranked biomarkers by gradient boosting were interleukin-6, symmetric dimethylarginine, LDL-triglycerides [LDL-TG], apolipoprotein B48, palmitoleic acid, small dense LDL, alkaline phosphatase, and asymmetric dimethylarginine. In Bayesian analysis, LDL-TG was directly linked to atherosclerosis in over 95% of the ensembles. Genetic variants in the genomic region encoding hepatic lipase (LIPC) were associated with LIPC gene expression, LDL-TG levels and with atherosclerosis. Triglyceride-rich LDL particles, which can now be routinely measured with a direct homogenous assay, play an important role in atherosclerosis development.